Disrupting dignity : rethinking power and progress in LGBTQ lives - Engel, Stephen M.; Lyle, Timothy S. (LGBTQ politics series, 2021)
"In 2015, when the Supreme Court declared that gay and lesbian couples were entitled to the "equal dignity" of marriage recognition, the concept of dignity became a cornerstone for gay rights victories. In Disrupting Dignity, Stephen M. Engel and Timothy S. Lyle explore the darker side of dignity, tracing its invocation across public health politics, popular culture, and law from the early years of the HIV/AIDS crisis to our current moment. With a compassionate eye, Engel and Lyle detail how politicians, policymakers, media leaders, and even some within LGBTQ+ communities have used the concept of dignity to shame and disempower members of those communities. They convincingly show how dignity-and the subsequent chase to be defined by its terms-became a tool of the state and the marketplace thereby limiting its more radical potential. Ultimately, Engel and Lyle challenge our understanding of dignity as an unquestioned good. They expose the constraining work it accomplishes and the exclusionary ideas about respectability that it promotes. To restore a lost past and point to a more inclusive future, they assert the worthiness of queer lives beyond dignity's limits"--